AUTOMATIC VEHICLE DENSITY MONITORING SYSTEM - Gredy Christian Hendrawan Putra; Andreas Nugroho Sihananto, S.Kom., M.Kom. (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2025)
An Intelligent Traffic Control System simulation using CCTV based vehicle detection is proposed to optimize traffic lights in real time for improved efficiency and future implementation